Arctic Freshwater Biodiversity Monitoring Plan: Framework Document - Culp, J.; Gantner, N.; Gill, M.; Reist, J.; Sweetman, J.; Wrona, F. (Conservation of Arctic Flora and Fauna (CAFF), 2011)
This document provides an overview on the development of a Freshwater Expert Monitoring Group (FEMG) for the Circumpolar Biodiversity Monitoring Program (CBMP) along with timelines for development of the FEMG. Considerations for monitoring Arctic freshwater biodiversity are discussed, including types of stressors, various approaches to monitoring, and criteria used to choose appropriate metrics to measure biodiversity status and trends. Canadian freshwater researchers took the lead to provide expert advice for this international initiative by developing: 1) recommendations of the spatial scale of monitoring needed for Arctic Canada; 2) a strategic list of metrics that should be monitored as well as standardized methods to be used; 3) a summary of existing and recent aquatic programs in the Arctic; and 4) discussions on issues surrounding data management and archiving.